Optimalisasi Pemanfaatan Aset Desa Guna Meningkatkan Pendapatan Asli Desa Makmur Kecamatan Pangkalan Kerinci Kabupaten Pelalawan Provinsi Riau - Dwi Agus Sumarno; Riko Wijaya; Hendayana Hendayana (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2025)
Village assets have significant potential to serve as a source of Village Original Income (PADes) if managed optimally. However, Desa Makmur, despite its abundant assets, has not yet succeeded in leveraging them effectively as a source of PADes. This study aims to examine the optimization of village asset utilization, the challenges encountered, and the efforts undertaken to overcome them. A descriptive, qualitative method was employed, with the researcher serving as the primary instrument. The findings indicate that the Village Government of Makmur, supported by the Pelalawan Regency Government, has made various efforts to manage assets through documentation, mapping, the formulation of regulations such as Regent Regulation No. 76 of 2018, and technical training on asset management. Nevertheless, several obstacles remain, including the unclear legal status of assets, limited human resource capacity, insufficient budget, the lack of a centralized asset data management system, weak asset security by the government, and limited communication from the central government regarding asset management regulations. To address these challenges, the regency government, village government, local communities, and the private sector have undertaken collaborative efforts to optimize the utilization of village assets.